\(\left(1+x^2\right)\left(1+y^2+4xy\right)+2\left(x+y\right)\left(1+xy\right)=25\)
\(\Leftrightarrow\) \(x^2+2xy+y^2+x^2y^2+2xy.1+1+2\left(x+y\right)\left(1+xy\right)-25=0\)
\(\Leftrightarrow\) \(\left(x+y\right)^2+2\left(x+y\right)\left(1+xy\right)+\left(1+xy\right)^2-25=0\)
\(\Leftrightarrow\) \(\left(x+y+1+xy+5\right)\left(x+y+1+xy-5\right)=0\) \(\Rightarrow\) \(\left\{{}\begin{matrix}x+y+xy=-6\\x+y+xy=4\end{matrix}\right.\)
nếu \(x+y+xy=-6\Rightarrow\left(x+1\right)\left(y+1\right)=-5\)
( vì \(x,y\in Z\) nên \(x+1;y+1\in Z\) )
ta lập bảng :
\(x+1\) | \(1\) | \(5\) | \(-1\) | \(-5\) |
\(y+1\) | \(-5\) | \(-1\) | \(5\) | \(1\) |
\(x\) | \(0\) | \(4\) | \(-2\) | \(-6\) |
\(y\) | \(-6\) | \(-2\) | \(4\) | \(0\) |
\(\Rightarrow\) \(x;y\in\left\{\left(0,6\right);\left(4,-2\right);\left(-2,4\right);\left(-6,0\right)\right\}\)